Determination of hydraulic parameters of non-linear consolidation clay layers by type curve method - Wang, Ruizhe; Li, Zhaofeng; Xu, Mo; Zhang, Qiang; Illman, Walter A.; Li, Hao (Frontiers in Earth Science, 2023)
The consolidation of clay layers is of great significance for groundwater environmental protection, groundwater storage utilization, and land subsidence. In this study, the governing equation for the excess pore water pressure during the nonlinear consolidation process of clay layers under load conditions is obtained based on the one-dimensional nonlinear consolidation theory. Analytical solutions are then derived for clay layers with single or double drainage caused by the dissipation of the excess pore water pressure. With these analytical solutions, the groundwater dynamics and deformation of the clay layer are analyzed. Correspondingly, a type curve method is proposed to calculate the hydraulic parameters of the clay layer through laboratory experiment, which verifies the reliability of the analytical solutions. The study results show that the deformation of the clay layer predicted by the nonlinear consolidation theory is smaller than that predicted by the linear consolidation theory. The deformation of the clay layer increases with the increase in the thickness of the clay layer, the compressive index, and the loading pressure, while decreases with the increase in the initial void ratio and the initial effective stress. The stable time, at which the consolidation of the clay layer is completed, increases with the increase in the compression index and the thickness of the clay layer, while decreases with the increase in the initial void ratio, the initial effective stress, and the initial hydraulic conductivity. It does not vary with the load pressure. Conclusively, the deformation prediction based on the nonlinear consolidation theory is more accurate and applicable to further load pressures.